Variabilidade climática e meteorológica na distribuição de Scarabaeinae coprófagos - Tissiani, Ana Silvia de Oliveira (2014)
The dung beetles have ecological relevance because, due to its association with the feces of mammals contribute to nutrient cycling and control parasites. Thus, knowledge of the factors that determine their geographical distribution utilities have important practical, towards the use of these beetles as allies in agricultural production systems and selection of areas for biodiversity conservation programs. The goal that was sought with the execution of this work was to contribute to the understanding of the association between the distribution of dung with the weather and climate scarabs, first evaluating meteorological characteristics which interfere in the presence of the species locally, which are species in pastures and which the adjacent forested habitats and what causes the onset of activity of dungrolling. Next, we investigated what are the dung beetles commonly found in Brazilian pastures and what their regional climatic tolerance, allowing the identification of these species which are more suitable for use in biological control of pests in livestock. The results were generated based on the construction of the multivariate regression trees, and maps of geographic distribution patterns generated by the MaxEnt program. Locally climatic variations explained between 23 and 47% of the distribution of the fauna of dung - rolling beetles, with species showing marked population fluctuations throughout the sampling period. Dichotomius bos, Dichotomius nisus, Ontherus appendiculatus, Trichillum externepunctatum, and Digitonthophagus gazella are more constant in the grasslands of north to south of Brazil and therefore are considered the most important dung-rolling beetles for this kind of environment. These five species have a limited distribution primarily by the minimum temperature of the coldest month, followed by precipitation of the warmest quarter or coldest quarter.